(untitled) (e-Journal of Linguistics, 2024)
This study was aimed to see the Influence of EGRA technique on students’ Grammar Mastery at the eighth grade students of MTs Istiqlal Delitua. The objective of this study is to get the empirical data of the differences between students` score grammar test that were taught by using EGRA technique and the students were not. The population of this study consists of 126 students. The sampling process of this research is cluster random sampling technique. The researcher took two classes, VIII D as experimental class consisted of 32 students and VIII C as control class consisted of 31 students. The design of this study is a quantitative method using quasi-experimental design (non-equivalent control group) with two group classes, namely experimental class and control class. The data was collected through pretest and posttest. It aimed to know whether the EGRA technique in teaching grammar can improve students` grammar mastery. The research findings demonstrate that the t-test value is 10.83, which is significantly higher than the t table value of 1.670 (3.925 > 1.670). This signifies that the use of the EGRA technique is effective in enhancing students’ grammar mastery among the eighth-grade students of MTs Istiqlal Delitua. Consequently, the alternative hypothesis (Ha) is accepted, while the null hypothesis (H0) is rejected